Procedure of Letter of credit (LC), Import, Export and Local trade of Mutual Trust Bank - Chowdhury, Sakha (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.